Organizational and Legal Principles of Soviet Militia Dispatch Center’s Functioning during 1969–1991 - Halkin, D. V.; Halkina, O. M. (Bulletin of Kharkiv National University of Internal Affairs, 2020)
The normative and legal provision, organization and activity of militia dispatch centers of Soviet Ukraine in 1969–1991 have been studied. Various forms, methods and directions of activity of militia dispatch centers in 1961–1991 have been analyzed; and the activity of the militia in ensuring the protection of public order and the fight against crime has been reconsidered. The author has characterized the functions of militia dispatch centers, which were performed by them in the period from 1969 to 1991. The peculiarities of personnel and logistical provision of the militia dispatch centers in the specified historical period have been highlighted. The analysis of archival materials has demonstrated that the implementation of the function of the dispatch center was associated with the implementation of an increased number of tasks. However, the combination of the duties of a duty officer with performing the duties in another position led to the overburdening of a militiaman, which had a negative impact on law enforcement activity. Improving the organizational forms of the Soviet militia dispatch centers was carried out in several areas: 1) the creation of regular police units in all militia agencies, the number of which depended on the population, as well as changes in the operative situation; 2) increase in the number of regular shifts; 3) bringing the premises, equipment and logistics of dispatch centers in line with the established requirements; 4) the introduction of additional structures within dispatch centers, caused by an increase in the workload on dispatch centers as a result of the growth in crime rates; 5) increase of requirements to personnel of dispatch centers. In terms of reforming the law enforcement system, miscalculations and mistakes of the past years should be avoided. The specifics of dispatch centers’ activity is that it represents the interests of all services, combines the goals and objectives of public order, prevention and detection of crimes, as well as coordinates their actions in case of emergencies. The efficiency of crime detection, assistance to victims and detention of perpetrators depends on the effective organization of interaction between services and units. Thus, the creative use of obtained experience to improve the activities of the dispatch centers of internal affairs agencies will to some extent avoid mistakes and miscalculations made in previous historical periods.